The patacon plan: A complementary currency for Buenos Aires economic development - Mario, Agustin Angel (2025)
The province of Buenos Aires (PBA) has a population of more than 18 million inhabitants, around 40 percent of the national total. However, it receives only about 20 percent of the tax revenue shared with the provinces – which, in addition, as we said, will be reduced as a result of the federal public spending. The phrase “I’m going to leave them without money” recently made known by President Milei regarding the provincial governors, illustrates the seriousness of the situation, which is expected to be especially acute in the province of Buenos Aires. An alternative to avoid the social outbreak to which the national government’s economic policy leads the Argentinian economy is to implement a complementary currency. The Patacon Plan presented here would provide financial independence to the PBA: since it does not imply any need for financing in a currency of which it is a user... The Patacon would operate continuously in a small, open economy, with multiple other currencies trading around it simultaneously. More importantly, it would allow the PBA to act counter-cyclically, increasing the deficit when employment declines, and vice versa; that is, functioning as an automatic stabilizer, maintaining full employment and a currency of stable value.